Prospects of Creating the Reflective Teacher for Continuing Professional Development (CPD) - Yousra Ali Aghanimi; Fawzia Mohamed Elwafi; Fahima Mohamed Bannur (FOSTER: Journal of English Language Teaching, 2021)
Teacher self-evaluation is an important dimension in the overall evaluation activities in educational programs. However, this dimension is often overlooked and not given its right share of importance. Teacher self-evaluation is neither included in teacher training programs nor is considered a basic requirement from teachers as they develop in their careers. The significance and value of teacher self-evaluation as a core element in continuing professional development requires that self-evaluation proceed all other forms of evaluation. To support the claim that teacher self-evaluation is a missing element in the area of investigation, the researchers conducted a study which adopted a survey that involved eleven schools and 86 Libyan teachers. The results of the study showed that while many teachers perform some sort of self-reflection about their teaching, they do not recognize self-evaluation as a basic requirement in developing their career. When the effectiveness of teacher self-evaluation was probed in contrast to external evaluation, most teachers agreed that teacher self-evaluation could play a far more vital role in continuing professional development.